2009
DOI: 10.1021/jf8029397
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Fingerprint Analyses of Chinese Sweet Tea Plant (Rubus suavissimus S. Lee)

Abstract: Quality of botanical food is increasingly assessed by the content of multiple bioactive compounds. In this study we report, for the first time, an HPLC fingerprinting method for the quality evaluation of Rubus suavissimus leaves possessing multiple bioactivities. Five constituents, gallic acid, rutin, ellagic acid, rubusoside, and steviol monoside were quantified and used in developing qualitative chromatographic fingerprints. The limits of detection and quantification ranged from 0.29 μg/mL to 37.86 μg/mL. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 25 publications
(31 reference statements)
2
41
1
Order By: Relevance
“…The optimization of the chromatographic conditions led to a good resolution of adjacent peaks of the flavonoids in this study when compared to other methods previously described for the quantification of these compounds in crude plant materials (Chou et al, 2009;Batista et al, 2010).…”
Section: Resultsmentioning
confidence: 60%
“…The optimization of the chromatographic conditions led to a good resolution of adjacent peaks of the flavonoids in this study when compared to other methods previously described for the quantification of these compounds in crude plant materials (Chou et al, 2009;Batista et al, 2010).…”
Section: Resultsmentioning
confidence: 60%
“…The similarity ranges between 0 and 1, with 0 meaning no similarity between the fingerprints and 1 identical fingerprints. Besides similarity analysis based on the entire fingerprint [39,45,87,92,102,116,117,122], the relative retention time (RTT) and relative peak area (RPA) of characteristic peaks can also be used [197]. Over the years, new methodologies for similarity analysis of fingerprints have been developed.…”
Section: Similarity Analysismentioning
confidence: 99%
“…Seasonal variations in natural compounds are fairly common and can contribute to variations of the finished products (Chou et al, 2009). Black et al (2011 reported that there were significant seasonal variations in fifteen constituents of Northern Labrador Tea (Rhododendron tomentosum ssp.…”
Section: Compoundsmentioning
confidence: 99%
“…In this study, the content of isoquercitrin was 0.23 mg/g in HHF provenance, and it was much lower than the report from Fang et al (2011), likely caused by seedling ages and extraction methods. Therefore, JXS is selected to be the optimal provenance based on the quantification of seven bioactive compounds.Seasonal variations in natural compounds are fairly common and can contribute to variations of the finished products (Chou et al, 2009). Black et al (2011 reported that there were significant seasonal variations in fifteen constituents of Northern Labrador Tea (Rhododendron tomentosum ssp.…”
mentioning
confidence: 99%